Entre halago y acoso: percepción de las estudiantes mujeres de la Carrera de Sociología, PAO ii 2023. - Gómez Mora, Sharon Mishell (2024)
n today's society, harassment is still considered a normalized practice to the external beauty of women as ways of relating between individuals, this is because society has minimal knowledge about the difference between the two, but at the same time, it can be considered a social problem, where it is important to reflect on the issue and generate knowledge to people against the characteristics of harassment and flattery in a generalized way in public and private institutions. The main purpose of this research is to learn about the process of normalization and invisibilization of certain macho behaviors of power that reoccur in today's society, while knowing the perceptions of the students of the sociology career and what would be the procedure if they were to witness the harassment. The methodology to be used is mixed, since it combines the quantitative and qualitative method by trying to collect, integrate and analyze data and information through a research instrument which in this case would be the survey and, at the same time, bibliographic documents that support the topic in question, in the same way it is intended to test the hypothesis put forward in the research work in a clear and objective manner. Finally it is concluded that flattery are terms that are part of a social interaction, which is located between a thin line of violence, where today's society justifies men to make invisible harassment, patriarchy and gender violence, such macho actions, can be a form of aggression for the recipient, as it can be authoritarian and aggressive. For example; the way of seeing, approaching and touching constitutes all types of harassment where the corresponding and legal actions that the case deserves should be taken. Keywords: Harassment, Flattery, Gender violence, Social problem, Patriarchy.